a) rewrite dy/dx = 3x^2 – 20x + 29
to dy = (3x^2 – 20x + 29)dx
Then integrate it
y = INT((3x^2 – 20x + 29)dx)
Remember there's a constant K in your function after integration
say y = g(x) + K
Find K by puting y = 6, x = 2 into y = g(x) + K.
(If you don't know how to integrate it, please open your notebook, it's quite simple)
b) Substitute x = 4 in y = g(x) + K, you'll get y = 0
So the curve passes (4, 0)
c)Tangent at P:
You know dy/dx = 3x^2 – 20x + 29
Plug x = 2 to get y'(2)
So y = y'(2)(x-2) + 6.
d) Tangent at Q is parallel to tangent at P
=> it has same gradient y'(2)
You'll find xQ by solving this equation
y'(2) = 3x^2 – 20x + 29
and eliminate x = 2 since xP = 2.
Then you'll get yQ = g(xQ) + K
Sorry I can't calculate everything for you, just show you the way to do it